Distribution of Turkish Helophorus fabricius, 1775 (Coleoptera, Hemophoridae) I. Subgenus Rhopalhelophorus, with two new records - İncekara, Ümit; Mart, Abdullah; Erman, Orhan (My University, 2004)
Two newly recorded Helophorus Fabricius, 1775 species for the Turkish fauna, Helophorus (Rhopalhelophorus) paramontanus Angus, 1985 and H. (R.) kerimi Ganglbauer, 1901 are compared against Turkish specimens (private collection). A list of subgenus Rhopalhelophorus species known from Turkey and their distribution in Turkey and in the world is presented.
Keywords: Fauna; Helophorus paramontanus; Helophorus kerimi; Helophoridae; taxonomy; new geographic records; geographical distribution